Étude in vitro et in vivo des activités de Moringa oleifra de la région d'EL Oued - BACHIR Rayane; SEDIRA Alia (جامعة الوادي university of eloued, 2024)
This study aims to evaluate the biological activity of Moringa oleifera extracts from the Ouargla region (El Oued) through a series of physical and chemical analyses, as well as in vitro and in vivo biological tests. The study focused on exploring the properties of these extracts as natural dietary supplements with antioxidant, anti-inflammatory, analgesic effects, and potential anxiolytic and antidepressant activities. In the first stage, the proportions of mineral and organic matter in both extracts were determined, revealing a higher content of carbohydrates and minerals in sample E, while sample G showed a relatively higher concentration of proteins. In the FRAP test, sample E exhibited greater iron-reducing capacity with an EC₅₀ value of 126.175 µg/ml, whereas sample G demonstrated better effectiveness in the DPPH test with an IC₅₀ value of 22.515 µg/ml, reflecting different antioxidant mechanisms between the two extracts. FTIR analysis confirmed the presence of active functional groups such as hydroxyl and carbonyl groups, while DRX analysis revealed partial crystalline structures of the bioactive compounds. In the in vivo biological tests, the behavioral and analgesic activities of the extracts were evaluated at two doses (40 and 80 mg/kg). In the forced swim test, sample G at 80 mg/kg showed a mobility time of 287.97 seconds, indicating antidepressant activity comparable to the reference treatment،thereby reinforcing its effectiveness as an antidepressant through central mechanisms. Regarding the analgesic effect، sample G demonstrated significant effectiveness in the hot plate test by delaying the pain response, indicating a central mechanism of action.
Keywords: Moringa oleifera; biological activity; analgesic activity; antidepressant activity